How CEO Work Experience Shapes Carbon Emission Disclosure: The Role of Board Size - Krisyadi, Robby; Dyno, Nestroy; Chandra, Budi (Journal of Economics and Business UBS, 2025)
This study examines the influence of CEO work experience on carbon emission disclosure (CED) and evaluates the moderating role of board size in Indonesian listed firms. Using a quantitative approach, the research analyzes secondary data from annual and sustainability reports of 69 companies from 2019 to 2023, applying panel regression to test the direct impact of CEO work experience and its interaction with board size. The results show that CEO work experience negatively affects CED, suggesting that more experienced CEOs tend to prioritize financial outcomes and risk avoidance over environmental transparency. This conservative orientation contributes to reluctance in engaging with voluntary carbon reporting. The findings further reveal that board size significantly moderates this relationship. Larger boards strengthen the negative effect of CEO work experience, as coordination challenges and reduced monitoring effectiveness provide experienced CEOs with greater discretion to limit disclosure. This highlights the critical role of governance structures in shaping sustainability reporting outcomes. The study acknowledges limitations, particularly the focus on only two variables indicating that future research should include additional governance mechanisms and executive characteristics to obtain a more comprehensive understanding of disclosure behavior. Practically, the results suggest that firms and regulators need to reconsider board composition to ensure effective oversight capable of counteracting managerial conservatism and supporting transparent carbon reporting. Overall, this study contributes to the literature by integrating executive attributes with governance dynamics, providing new evidence on how board size can influence the transparency of environmental disclosures in emerging markets such as Indonesia.